Complex sleep apnea at auto‐titrating CPAP initiation: prevalence, significance and predictive factors. (2nd July 2015) - Neu, Daniel; Balkissou, Adamou Dodo; Mairesse, Olivier; Pefura‐Yone, Eric Walter; Noseda, André
Abstract: Introduction: Obstructive sleep apnea (OSA) patients may develop central respiratory events under continuous positive airway pressure (CPAP), referred to as complex sleep apnea (CompSA). Objective: We aimed to assess prevalence and predictive factors of complex apnea and to evaluate treatment response to CPAP. Methods: Within a retrospective cohort study, we assessed clinical data of OSA patients, attending the sleep lab during a 15‐months period. Included participants underwent two consecutive polysomnographies; baseline diagnosis and treatment trial. Complex apnea patients, defined by a central apnea index ≥ 5 per hour during pressure auto‐titration, were compared to remainders. Results: Among 263 included patients, the prevalence of complex apnea was 9.1%. The mean apnea hypopnea index only dropped from 52.7 to 39.9 per hour in CompSA patients, while it improved from 40.9 to 7.3 in patients without CompSA. Although a decreased sleep‐fragmentation under CPAP was observable in both groups, the enhancement of Non‐REM sleep was superior in patients without CompSA. The CompSA patients showed higher median apnea‐hypopnea, mixed apnea and central apnea indices at baseline and displayed higher rates of comorbid heart failure and obstructive pulmonary disease, but no higher severity of associated daytime fatigue and sleepiness symptoms. Conclusion: Despite evidenced partial improvement of obstructive events, nocturnal hypoxemia and sleep fragmentation, the occurrence of complex apnea presented here as a clear therapeutic failure of auto‐titrating CPAP and was associated with heart failure, COPD and higher central and mixed apnea indices at baseline.